Modelling a dispute hearing between an investor and the public concerned in administrative courts of the Republic of Lithuania - Šostak, Olga Regina; Makutėnienė, Daiva (Technological and Economic Development of Economy, 2013)
The article discusses possible effects on the success of an investment project when rights of the public concerned have been infringed during construction planning. The administrative proceedings defending the rights of the public concerned infringed during territorial planning have been analysed for that purpose. For any construction project, judicial dispute is an undesirable risk factor and can disrupt the entire project. The article, therefore, looks into an actual dispute that reached the court and took place between an investor and the public concerned. The negative effects of this judicial dispute, both on the investor and the public concerned, have been determined. The investor's blunders that prevented any chance of escaping the judicial dispute and led to several years of litigation have been also determined. The article looks into the behaviour of disputing parties at various stages of the judicial dispute. Based on the research, a conceptual model was crafted to enable analysis of formal model behaviour in future studies and to build a complex system that would facilitate any construction project with planning and application of preventive measures that would mitigate the risk of a judicial dispute as early as during the first project planning stage.